Are cannabinoids taken orally an effective treatment for adults with chronic neuropathic pain?. Issue 1 (January 2017) - Wenstrup, Thomas; Sheth, Bansari
Abstract : EVIDENCE‐BASED ANSWER : The answer is unclear. Nabilone and nabiximols, as adjuncts to any stable analgesia regimen including opioids, tricyclics, and anti‐inflammatory medications, reduce neuropathic pain by 1 to 2 points more than placebo on 11‐point pain scales. However, nabilone is not as effective as dihydrocodeine when the 2 are compared directly (SOR: B, small RCTs).